Odpowiedzi

2009-11-04T19:20:45+01:00
A) b2- 36 = (b-6)(b+6)
b) 49-y2 = (7-y)(7+y)
c) 4x2-25y2 = (2x - 5y)(2x + 5y)
d) m2-16n2 = (m - 4n)(m+4n)
e)a2b2-2 = (ab - √2)(ab + √2)
f) 9-x4v2 = (3-x²v)(3+x²v)
g) (4ab)2-0,01x6 = (4ab - 0,1x³)(4ab + 0,1x³)
h) x4-16 = (x² - 4)(x²+4)
i) 3-z2y6 = (√3 - zy³)(√3 + zy³)
15 4 15
  • 0rdi
  • Początkujący
2009-11-04T19:20:46+01:00
(b-6)(b+6)
(7-y)(7+y)
(2x-5y)(2x+5y)
(m-4n)(m+4n)
(ab-pierwiastek z 2)(ab+pierwiastek z 2)
(3-x2v)(3+x2v)
(4ab-0,1x3)(4ab+0,1x3)
(x2-4)(x2+4)
(pierwiastek z 3-zy3)(pierwiastek z 3-zy3)
2 5 2
2009-11-04T19:24:39+01:00
A) b2- 36= (b-6)(b+6)
b) 49-y2= (7-y)(7+y)
c) 4x2-25y2= (2x-5y)(2x+5y)
d) m2-16n2= (m-4n)(m+4n)
e)a2b2-2= (ab-√2)(ab+√2)
f) 9-x4v2= (3-x²v)(3+x²v)
g) (4ab)2-0,01x6= 16ab-0,1x⁶=(4√a√b-0,1x³)(4√a√b+0,1x³)
h) x4-16= (x²-4)(x²+4)
i) 3-z2y6 =(√3-zy3)(√3+zy³)
1 5 1